INSTRUCTORS’ STRATEGIES OF SMAGA ENGLISH CLUB (SEC) IN MOTIVATING STUDENTS IN LEARNING SPEAKING AT SMA N 3 PONOROGO IN THE ACADEMIC YEAR OF 2018/2019 - Risqi Ekanti Ayuningtyas Palupi; Lusi Ruspitasari; Siti Asiyah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2019)
This research aimed at investigating the Strategy used by Instructors of SEC (SMAGA English Club) 2018.Teaching English Speaking at Student of EFL is the most difficult thing for the Instructors. Language teaching strategies should be fun and enjoyable because learning language will be easier by using a good method and strategy that help language learners easier to understand. Every student will have different character in understanding a material. Therefore, Instructors have to facilitate them as good as possible.The Instructors strategy will influence to language learners understanding. In conducting the research, the researcher used descriptive qualitative research. observation, interview and documentation were the data collection technique. After data has been collected, the researcher analysed the data. The researcher took step of it started from reducing the data, display the data and the last drawing conclusion. This research took subjects of two Instructors of SMAGA English Club of SMAN 3 of Ponorogo the SEC consist of two divisions, general division and competition division. The data were collected from the observation, interview and documentation that organized based on research problems. Then researcher described the result.The results of that data were analysed to understand what the instructors’ strategy in motivating student’s speaking is. The researcher found that the student of SMAN 3 of Ponorogo have a good motivation in learning speaking and the strategy is used by two instructors are socio affective strategy and cognitive strategy. When applying socio affective strategy instructor used same games, the games are scrabble, tongue twister, who am I? and command games. Instructors also apply cognitive strategies by practice and repetition. In addition, the results of their strategy are for the general division they are getting better in speaking and for the competition division the student got some achievements that reach in some competition.By this research researcher suggested for instructors, students and other researcher. Instructors have to use appropriate strategy in teaching. Students have to more understand about speaking skill by instructor’s strategy. For other researcher can use the result of the research as the references for further research with different discussion domain of instructor’s teaching.